Recent Trends in Malaria Vaccine Research Globally: A Bibliometric Analysis From 2005 to 2022 - Muhammad Chutiyami (Journal of Parasitology Research)
Conclusion: The last one and half decades have seen a significant increase in malaria vaccine research and citations, mainly targeting vaccine development, safety, and efficacy in Africa. This necessitates more international efforts to improve the vaccines’ effectiveness considering different Plasmodium species.